COVID-19 PATHOPHYSIOLOGY PREDICTS THAT ISCHEMIC STROKE OCCURRENCE IS AN EXPECTATION, NOT AN EXCEPTION: A SYSTEMATIC REVIEW - Annurul Maulidia, Agnes; Rimbun Silitonga, Anni Rota; Yuni Kurniawati, Media (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Clinical reports of neurological manifestations associated with severe coronavirus disease 2019 (COVID-19), such as acute ischemic stroke (AIS) are increasing rapidly. However, there are comparatively few studies investigating the potential impact of immunological responses secondary to hypoxia, oxidative stress, and excessive platelet-induced aggregation on the brain.Aim: This study attempted to elucidate potential pathophysiological mechanisms associated with peripheral and consequential neural (central) inflammation leading to COVID-19-related ischemic strokes. Methods: A systematic search strategy was conducted across several electronic reference databases (MEDLINE, Cochrane Library, CINAHL) and included articles published between January 2000 and August 12th, was carried out up to August 15th, 2020. Duplicate publications, review articles, and incomplete articles were excluded.Results: The databases search identified a total of 1.539 articles (Table 1) and resulted in 672 articles after duplicates removed. Of these, 206 articles passed the screening process, resulting in 20 articles for full-text assessment. Among them, 10 articles did not evaluate the outcome of interest and insufficient details. Hence, we found 10 appropriate studies included. Conclusion: This study affirms that the immunological contribution to the pathophysiology of COVID-19 is predictive of the neurological sequelae particularly ischemic stroke, which makes it the expectation rather than the exception.